Enzymatic Synthesis of Phloretin α‐Glucosides Using a Sucrose Phosphorylase Mutant and its Effect on Solubility, Antioxidant Properties and Skin Absorption. Issue 12 (6th May 2021) - Gonzalez‐Alfonso, Jose L.; Ubiparip, Zorica; Jimenez‐Ortega, Elena; Poveda, Ana; Alonso, Cristina; Coderch, Luisa; Jimenez‐Barbero, Jesus; Sanz‐Aparicio, Julia; Ballesteros, Antonio O.; Desmet, Tom; Plou, Francisco J.
Abstract: Glycosylation of polyphenols may increase their aqueous solubility, stability, bioavailability and pharmacological activity. Herein, we used a mutant of sucrose phosphorylase from Thermoanaerobacterium thermosaccharolyticum engineered to accept large polyphenols (variant TtSPP_R134A) to produce phloretin glucosides. The reaction was performed using 10% (v/v) acetone as cosolvent. The selective formation of a monoglucoside or a diglucoside (53% and 73% maximum conversion percentage, respectively) can be kinetically controlled. MS and 2D‐NMR determined that the monoglucoside was phloretin 4'‐ O ‐α‐D‐glucopyranoside and the diglucoside phloretin‐4'‐ O ‐[α‐D‐glucopyranosyl‐(1→3)‐ O ‐α‐D‐glucopyranoside], a novel compound. The molecular features that determine the specificity of this enzyme for 4'‐OH phenolic group were analysed by induced‐fit docking analysis of each putative derivative, using the crystal structure of TtSPP and changing the mutated residue. The mono‐ and diglucoside were, respectively, 71‐ and 1200‐fold more soluble in water than phloretin at room temperature. The α‐glucosylation decreased the antioxidant capacity of phloretin, measured by DPPH and ABTS assays; however, this loss was moderate and the activity could be recovered upon deglycosylation in vivo . Since phloretin attracts a great interest in dermocosmetic applications, we analyzed the percutaneous absorption of glucosides and the aglycon employing a pig skin model. Although the three compounds were detected in all skin layers (except the fluid receptor), the diglucoside was present mainly on superficial layers. Abstract :